2003
DOI: 10.1067/mhn.2003.28
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Mandibulotomy: Midline Versus Paramidline

Abstract: There was no significant difference in the mandibulotomy-related complication rate between midline and paramidline mandibulotomies. Paramidline mandibulotomy, which preserves the geniohyoid and genioglossus muscles, should be a better function-preserving operation than midline mandibulotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 11 publications
2
39
0
7
Order By: Relevance
“…The authors had reviewed 313 mandibulotomies performed between 1959 and 1988 with emphasis on indications, complications, and modifications in technique. In a comparative study between these two types, Tsung SD et al [14] did not find any differences that were statistically significant. Amin MR et al [12], however, concluded straight midline osteotomy to be advantageous with no significant complications seen within 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors had reviewed 313 mandibulotomies performed between 1959 and 1988 with emphasis on indications, complications, and modifications in technique. In a comparative study between these two types, Tsung SD et al [14] did not find any differences that were statistically significant. Amin MR et al [12], however, concluded straight midline osteotomy to be advantageous with no significant complications seen within 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of malignant transformation seems to be higher in patients older than 40 years of age, men, and patients with solitary nodules over 2cms in diameter [8]. The risk of malignancy has, also, been linked to the frequency of recurrence [14,19]. An accurate diagnosis is essential for planning the best surgical approach to safely and radically remove PPS tumors Papadogeorgakis N et al [20] considered five main parameters in selecting the best approach in treating tumors of the PPS including the proximity and the projection of the tumor to the oropharyngeal wall or, the neck, the size of the tumor, the suspicion of malignancy, the vascularity and relation of the tumor to the neck neurovascular bundle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional and oncological outcomes have been good, and in carefully selected patients, TORS provides locoregional control in the confined surgical anatomy of the upper aerodigestive tract, without the morbidity of wide surgical access or speech and swallowing impairment that often accompanies high dose radiation 10,11 . Because most TORS defects result from early stage tumours and are consequently small, reconstructive efforts have often been limited to healing by secondary intention.…”
Section: Implantologymentioning
confidence: 99%